2019
DOI: 10.1111/acps.13011
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence in first episode psychosis: the role of pre‐onset subthreshold symptoms

Abstract: JL. Medication adherence in first episode psychosis: the role of pre-onset subthreshold symptomsObjective: The experience of pre-onset subthreshold psychotic symptoms (STPS, signifying a clinical high-risk state) in first episode psychosis (FEP) predicts poorer outcomes during treatment, possibly through differential adherence to medication. We explored whether adherence differs between FEP patients with and without pre-onset STPS. Methods: Antipsychotic medication adherence was compared in 263 STPS+ and 158 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 83 publications
0
6
0
1
Order By: Relevance
“…While there were no clinical or functional differences at baseline (entry to early intervention services) between patients with FEP with and without prior CHR-P states, such differences emerged after 1 year of early intervention services: those with preonset symptoms consistent with a CHR-P state had poorer psychotic symptom outcomes and global functioning (52). Furthermore, there is more frequent nonadherence to antipsychotic medication in the preonset/CHR-P state group (although without corresponding differences in insight) (53). Since this work involved retrospective assessments, it is possible that FEP cases without evidence of a preonset CHR-P phase exhibited a recall bias and that the true prevalence of symptoms consistent with a CHR-P state was substantially higher than measured.…”
Section: Resultsmentioning
confidence: 99%
“…While there were no clinical or functional differences at baseline (entry to early intervention services) between patients with FEP with and without prior CHR-P states, such differences emerged after 1 year of early intervention services: those with preonset symptoms consistent with a CHR-P state had poorer psychotic symptom outcomes and global functioning (52). Furthermore, there is more frequent nonadherence to antipsychotic medication in the preonset/CHR-P state group (although without corresponding differences in insight) (53). Since this work involved retrospective assessments, it is possible that FEP cases without evidence of a preonset CHR-P phase exhibited a recall bias and that the true prevalence of symptoms consistent with a CHR-P state was substantially higher than measured.…”
Section: Resultsmentioning
confidence: 99%
“…In our opinion, the discrepancy between the fixed-effects and the random-effects model plausibly depends more on the bias in the estimates from smaller component studies introduced by the random-effects model rather than on real heterogeneity across studies. Thus, we think that the protective effect of exposure to ADs at baseline in CHR-P is real and should be considered in light of converging lines of research pointing to the fact that medication exposure is relevant for outcomes (Daneault et al, 2019; Raballo et al, 2020a, 2021a). Several hypotheses can be brought about to explain this effect of ADs.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that 45.1% of FEP patients are nonadherent to antipsychotic treatment and more likely to refuse medication at the first offer of treatment [ 30 ]. A recent study reported a 75.4% rate of nonadherence over 2 years of antipsychotic treatment in FEP patients [ 31 ]. Together with the protection and promotion of patients’ rights regarding treatment decisions, it is necessary to improve their treatment compliance after the onset of psychosis, based on evidence supporting the negative impact of the duration of untreated psychosis on prognoses [ 4 ].…”
Section: Discussionmentioning
confidence: 99%